(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article explores the influence of personal names, as a spiritual value of the Kyrgyz people, on personality formation and psychological development. It examines the psychological aspects of the tradition of naming a child and its impact on the infant’s personal development, self-awareness, and social adaptation. The study highlights the symbolic and educational significance of naming in Kyrgyz society and describes the psychological risks to national identity posed by the spread of Arabic names amid the strengthening of Islamic culture. The research employs methods such as psychological observation, content analysis, comparative analysis, and surveys. In the practical part, the semantic and socio-psychological aspects of the names of primary school students are analyzed. Statistical data are used to identify psychological trends in the formation of national self-consciousness among children. The results show that personal names are an important factor in personal identification and spiritual security. Kyrgyz names contribute to strengthening children’s national self-awareness and have a positive impact on their psychological resilience. The scientific report emphasizes the necessity of preserving Kyrgyz names and proposes national policy and educational measures in this direction.